Investigating the histological and structural properties of tendon gel as an artificial biomaterial using the film model method in rabbits - Kengo Shimozaki; Junsuke Nakase; Yoshinori Ohashi; Toru Kuzumaki; Tatsuya Yamaguchi; Kojun Torigoe; Hiroyuki Tsuchiya (Journal of Experimental Orthopaedics, 2022)
Abstract Purpose This study aimed to evaluate the properties of tendon gel by investigating the histological and structural differences among tendon gels under different preservation periods using a rabbit model. Methods Forty mature female rabbits were divided into four groups, each containing ten rabbits, on the basis of in‐vivo preservation periods of tendon gels (3, 5, 10, and 15 days). We created the Achilles tendon rupture models using the film model method to obtain tendon gels. Tensile stress was applied to the tendon gel to promote maturation. Histological and structural evaluations of the tendon gel were performed before and after applying the tensile force, and the results obtained from the four groups were compared. Results Although the day‐3 and day‐5 tendon gels before applying tensile stress were histologically more immature than the day‐10 and day‐15 gels, type I collagen fibers equivalent to those of normal tendons were observed in all groups after the tensile process. Based on the surface and molecular structural evaluations, the day‐3 tendon gels after the tensile process were molecularly cross‐linked, and thick collagen fibers similar to those present in normal tendons were observed. Structural maturation observed in the day‐3 tendon gels caused by traction was hardly observed in the day‐5, ‐10, and ‐15 tendon gels. Conclusions The day‐3 tendon gel had the highest regenerative potential to become a normal tendon by applying a traction force.